PERAN KEPALA KUA DALAM MENANGANI NIKAH SIRI DI DESA JUNREJO KOTA BATU - Muhammad Ihsan Fathoni; Ibnu Jazari; Shofiatul Jannah (Jurnal Hikmatina, 2022)
Marriage is an inner and outer bond between a man and a woman to live an orderly family life together. In Islamic law, a marriage is considered valid, that is, if it has fully fulfilled the pillars and conditions of marriage regulated in Islamic law. According to Article 1 of the 1974 Marriage Law, it is obligatory for people to have legitimate children and families in order to live happily in this world and the hereafter, under the auspices of God's love and joy. As stated in Article 1 of the Basic Marriage Law Number 1 of 1974 which states that "Marriage is an inner and outer bond between a man and a woman as husband and wife with the aim of forming a family happiness and eternity (household) from one birth.The purpose of this study is to describe how the implementation of siri marriage is, how the role of the head of the KUA is and to find out Siri marriage in the perspective of Positive Law and Islamic Law. This research method uses a qualitative approach with the type of field research. Sources of data come from direct interviews with the head of KUA, marriage administration staff and refer KUA Batu City, and 2 perpetrators of unregistered marriages, to obtain strong evidence to support the argument as well as secondary data that includes official documents, books, research results. .The results of the study stated that the implementation of unregistered marriages in Junrejo Village that occurred was due to several factors, including the low level of education and lack of knowledge and legal understanding about the importance of registering marriages, having had sex before marriage and the lack of education learned by the community. Meanwhile, the efforts made by the head of the KUA are conducting counseling on the registration of marriages and happy families to prospective brides and guardians, as well as socializing the importance of registering marriages and their negative impact on families, mothers and children through seminars and recitations held by the Ministry of Education and Culture. religion through representatives in the sub-district held in the community. Keywords: Unregistered marriage, Positive Law, Islamic Law.